Chapter Sviluppare identità di persone che apprendono - Striano, Maura (Studies on Adult Learning and Education, 2022)
Within the context of a reflection on learning from a lifelong and lifewide perspective, this paper intends to highlight the pedagogical need to focus on the individual and her or his resources as a prerequisite for starting and maintaining a fruitful "learning career". For this purpose, the construct of "learning identity" is explored in depth. Within the field of the "technologies of the self" it has been possibile to identify dedicated strategies and tools that can support the growth and evolution of this form of adult identity in support of a leaning that can nourish the different stages of life.